2021
DOI: 10.3390/toxics9080178
|View full text |Cite
|
Sign up to set email alerts
|

Formaldehyde in Hospitals Induces Oxidative Stress: The Role of GSTT1 and GSTM1 Polymorphisms

Abstract: Despite the toxicity and health risk characteristics of formaldehyde (FA), it is currently used as a cytological fixative and the definition of safe exposure levels is still a matter of debate. Our aim was to investigate the alterations in both oxidative and inflammatory status in a hospital working population. The 68 workers recruited wore a personal air-FA passive sampler, provided a urine sample to measure 15-F2t-Isoprostane (15-F2t-IsoP) and malondialdehyde (MDA) and a blood specimen to measure tumour necr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 74 publications
0
3
1
Order By: Relevance
“…In our study we found non-significant (p>0.05) association of GSTM1 and GSTT1 with oxidative stress and contradicting our findings (Ercegovac et al, 2015). According to several researches, deletion of the GSTT1 and GSTM1 genes is linked to an increase in lipid peroxidation indicators such MDA (Datta et al, 2010;Kumar et al, 2012;Ghelli et al, 2021).…”
Section: Influence Of Gstm1 and Gstt1 Genotype On Gsh And Gst Activitycontrasting
confidence: 96%
“…In our study we found non-significant (p>0.05) association of GSTM1 and GSTT1 with oxidative stress and contradicting our findings (Ercegovac et al, 2015). According to several researches, deletion of the GSTT1 and GSTM1 genes is linked to an increase in lipid peroxidation indicators such MDA (Datta et al, 2010;Kumar et al, 2012;Ghelli et al, 2021).…”
Section: Influence Of Gstm1 and Gstt1 Genotype On Gsh And Gst Activitycontrasting
confidence: 96%
“…Several research proved formaldehyde significantly decreased superoxide dismutase and glutathione peroxidase, increased lipid peroxidation with malondialdehyde formation, increased isoprostane levels, and TNF-α, as well as there was a dosing response relationship between lipid peroxidation index and formaldehyde concentration. 8,14 Rat exposed to formaldehyde inhalation showed higher MDA values than the control group, while Superoxide Dismutase (SOD) values were lower than those of the control group. There is a dose-response relationship between formaldehyde concentration and lipid peroxidation index.…”
Section: Introductionmentioning
confidence: 98%
“…However, Ghelli et al. ( 27 ) found that GSTT1 gene polymorphisms played a crucial role in the damage to oxidative stress in formaldehyde-induced oxidative stress. Through the above research, we believe that genes GPX3 and GSTT1 play an important role in the oxidative stress responses of tissues and organs, which may be potential targets for regulating oxidative stress during RIRIs.…”
Section: Discussionmentioning
confidence: 99%